Evaluasi Pelaksanaan Program Penyetaraan D-II Pendidikan Guru Sekolah Dasar - Primardiana Hermilia Wijayati (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Evaluation Study on the Implementation of D-II Equivalent Program of Elementary School Teacher Education. The study aimed to evaluate the implementation of D-II Equivalent Program of Elementary School Teacher Education, concerning the evaluation of the curriculum, students, teaching-learning process, academic staff, facilities, and the shortcomings. The study was carried out in Blitar and Jombang, involving 337 subjects comprising students, tutors, instructors of practical work, and supervisors. The data were collected through questionnaires, interviews, documentation study, and observation and then analyzed using statistics of percentages. The results indicate that the implementation of the curriculum is mostly relevant to the guidelines and that there are shortcomings in implementing the program, especially concerning the availability of the modules and the late acceptance of them.